(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
This research examines lived experiences and interpretations of dwelling in traditional Javanese Joglo houses through a phenomenological perspective. The Joglo represents Javanese architectural traditions embedded with cultural, social, and spiritual values, expressing cosmological principles and social stratification through its spatial arrangement. Although increasingly marginalized by modernization and urban development, the Joglo continues to hold cultural significance for communities maintaining ancestral traditions. The study seeks to reveal residents’ subjective experiences and the meanings they assign to everyday life within a Joglo, emphasizing two central phenomenological dimensions: the textural dimension, referring to what is experienced, and the structural dimension, describing how experience is lived. Using in-depth interviews with residents from three generational groups, the research documents narratives of dwelling within this environment. The findings demonstrate that the Joglo integrates cultural, spiritual, and material dimensions of architecture, influencing residents’ lifestyles and practices. The house is understood not only as a built form, but as a symbolic setting filled with values and significance. This study contributes to architectural preservation discourse in Indonesia by emphasizing the balanced relationship among people, space, and culture within Javanese society.